Pengaruh Pemberian Ekstrak Etanol Buah Pare (Momordica Charantia L.) Terhadap Penurunan Kadar Gula Darah dan Gejala Toksisitas Pada Mencit (Mus Musculus L.) - Khatarina Septi Amelia Putri; Nuning Nurcahyani; Dzul Fithria Mumtazah; M. Kanedi (PT. Hasba Edukasi Mandiri, 2025)
Hyperglycemia refers to elevated blood glucose levels above the normal range. It is caused by glucose accumulation in the blood that fails to enter cells, insulin hormone dysfunction, and hereditary factors. This condition can impair organ function. Several studies have shown that Momordica charantia contains compounds that stimulate the regeneration of beta cells, thereby increasing insulin production. This study aims to evaluate the effectiveness of ethanol extract from M. charantia fruit in lowering blood glucose levels and to observe any toxicity symptoms induced by the extract in mice, to assess its safety. The research used a Completely Randomized Design (CRD) involving six treatment groups with five replications each: K(-) without alloxan or test substances, K(+) induced with alloxan and treated with glibenclamide, and P1 to P4 induced with alloxan and administered M. charantia extract at doses of 5, 50, 300, and 2000 mg/kg body weight, respectively. Observed parameters included mean body weight, blood glucose levels, toxicity symptoms (behavioral changes), organ weight, and macroscopic examination. Results indicated that the ethanol extract of M. charantia effectively reduced blood glucose levels in alloxan-induced male mice. Group P4 (2000 mg/kg BW) showed the most significant reduction (129.5 mg/dL). No significant toxicity symptoms were observed in organ weight or macroscopic structure, suggesting that the ethanol extract of M. charantia is safe for use.